Nexo (2020)
The main goal was to develop a collection of furniture using old materials that were considered useless. All materials had different restoration processes for being used as the main ingredient of a specific production. By doing this, the materials gain a new meaning and a second life, by taking something considered as waist and giving it value. This project presented a more sustainable way of development, separating itself from the traditional manufacturing models.